"Selfie-ists" or "Narci-selfiers"?: A cross-lagged panel analysis of selfie taking and narcissism. (July 2016) - Halpern, Daniel; Valenzuela, Sebastián; Katz, James E.
Abstract: We examine the widely popular social phenomenon of "selfies" (self-portraits uploaded and shared in social media) in terms of the observed positive relationship between this individualistic form of social media usage and narcissism. We conducted a cross-lagged analysis of a two-wave, representative panel survey to understand whether narcissists take selfies as an outlet for maintaining their positive self-views (the self-selection hypothesis), or if by taking selfies' users would increase their level of narcissism (the media effect hypothesis). The findings, however, are consistent with both hypotheses, suggesting a self-reinforcement effect: whereas narcissist individuals take selfies more frequently over time, this increase in selfie production raises subsequent levels of narcissism. Highlights: This article examines the relationship between "selfies" and narcissism. A cross-lagged analysis of a two-wave suggests a self-reinforcement effect. Whereas narcissist individuals take selfies more frequently over time. This increase in selfie production raises subsequent levels of narcissism.